THE INFLUENCE OF SERVICE, PRICE, PRODUCT QUALITY ON INCREASING RESTAURANT SALES IGA BAKAR OEMIK IKA SIDOARJO JAWA TIMUR - Purwati, Andrian Octavia; Sutanto, J.E (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
The aim of this research is to determine the influence of service, price and product quality on increasing sales of the Iga Bakar Oemik Ika restaurant in Sidoarjo. This study uses a quantitative approach. The population used in this research were people who had made purchases at the Iga Bakar Oemik Ika restaurant in Sidoarjo with a sample size of 150 people, so the sampling technique used was purposive sampling technique. Data collection was carried out using an online research instrument (Google Form) using a Likert scale. The independent variables studied by researchers include service, price and product quality as well as the dependent variable, namely increased sales. Resea rchers processed the data using SPSS software to test the proposed hypothesis. The results of this research partially show that the service variable has a significant positive effect on increasing sales of Iga Bakar Oemic Ika Sidoarjo. The results of research on the price variable have a significant positive effect on increasing sales of Iga Bakar Oemik Ika Sidoarjo. And the results on the product quality variable significantly have a positive effect on increasing sales of Iga Bakar Oemik Ika Sidoarjo. And simultaneously shows that the variables of service, price and product quality influence the increase in sales of the Iga Bakar Oemic Ika restaurant in Sidoarjo. The results of this research imply the importance of improving service, adjusting prices and increasing product quality and increasing sales of the Iga Bakar Oemik Ika restaurant in Sidoarjo.